Komunikasi Orang Tua Dalam Pengasuhan Seksualitas pada Remaja Di Desa Sindangmekar Kecamatan Wanaraja Kabupaten Garut - Wa Ode Nurul Yani; Rodhiyat Fajar Salim (Dialektika, 2018)
Teenagers are faced with problems because in the body developing sex hormones that make his body full of turmoil and full of curiosity, including curious about sex. Information on sexuality in adolescents should be received from the right and proper source. Therefore, the role of parents in building communication in the care of sexuality in adolescents is needed. The method used in this research is qualitative research with phenomenology approach. Technique of data collecting by observation, interview, documentation, and triangulation (combination). Data analysis using Miles and Huberman model, by: data reduction, display data, and conclusion drawing / verification. Test data validity include test: credibility (internal validity), transferability (external validity), dependability (reliability), and confirmability (objectivity). The results describe the communication used by Mr. KQ's family is permissive and authoritative. The parenting of KQ's family sexuality is permissive and authoritative. In Mr. US family the communication patterns used are authoritative. The parenting of the sexuality of Mr. US family is permissive and authoritative. In Mr. DH's family the communication pattern is authoritative. The parenting of DH's family sexuality is permissive and authoritative.